Sport commitment among Malaysian racquet sports players / Arthur Ling Wei - Arthur, Ling Wei (2019)
Sport Commitment Model (SCM) has been widely used to understand the motivation of players to continue their involvement in sports. However, the factor that influence players’ commitment in racquet sports specifically were understudied especially in Malaysia. Therefore, this study aimed to utilize the Sport Commitment Model (Scanlan, Chow, Sousa, Scanlan, & Knifsend, 2016) framework to examine Malaysian players’ commitment in badminton, table tennis, tennis and squash. A total of 612 players (367 males, 245 females, μ age 30.32 ± 11.56) completed the Sport Commitment Questionnaire-2 which measured seven predictors and two dimensions of sport commitment. Results revealed that sport enjoyment was the main reason contributing to the players’ commitment in all sports (Badminton μ = 4.38 ± 0.51, Table tennis μ = 4.37 ± 0.54, Tennis μ = 4.79 ± 0.50, Squash μ = 4.63 ± 0.47). Data analyses showed significance difference in players’ enthusiastic commitment [F(3,608) = 45.44, p = 0.00] and constrained commitment [F(3,608) = 17.87, p = 0.00] across four racquet sports. However, significant difference were only found in enthusiastic commitment across gender in table tennis (t = 3.10, p = 0.04) and tennis (t = 2.63, p = 0.04). While only table tennis players showed significance difference in constrained commitment (t = -0.63, p = 0.04) across gender. Moreover, there were significant difference in enthusiastic commitment [F(3,608) = 9.00, p = 0.00] across age groups 11-20 vs. 31-40, 11-20 vs. >40, 21-30 vs. 31-40. Players’ constrained commitment [F(3,608) = 18.84, p = 0.00] differ across the age group of 11-20 vs. 31-40, 11-20 vs. >40 and 21-30 vs. 31-40. In conclusion, understanding sport commitment is important to facilitate players’ continuous participation in various racquet sports by taking into account on gender and age groups differences.